2022
DOI: 10.1038/s41564-021-01050-3
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics analyses of the ulcerative colitis gut microbiome link Bacteroides vulgatus proteases with disease severity

Abstract: Ulcerative colitis (UC) is driven by disruptions in host-microbiota homeostasis, however current treatments exclusively target host inflammatory pathways. To understand how host-microbiota interactions become disrupted in UC, we collected and analyzed six fecal or serum based –omic datasets (metaproteomic, metabolomic, metagenomic, metapeptidomic, and amplicon sequencing profiles of fecal samples and proteomic profiles of serum samples) from 40 UC patients at a single inflammatory bowel disease centre, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
118
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 194 publications
(126 citation statements)
references
References 109 publications
6
118
0
2
Order By: Relevance
“…The co-occurrence of Bacteroides with lower expression of interleukin signaling pathways is supported by experimental work that found potential anti-inflammatory and protective roles for these bacteria in the context of intestinal inflammation [34,39,40]. Still, the relative contributions of each of these species, as well as their behavior in the context of intestinal inflammation, remains elusive, although our data might reflect an overrepresentation of anti-inflammatory members [34-39,43]. The positive associations between Bacteroides and expression of metal ion response genes and metallothioneins (MTs) are intriguing in the context of IBD because aberrant MT homeostasis and intracellular zinc metabolism have been implicated in disease pathophysiology [4448].…”
Section: Resultssupporting
confidence: 52%
“…The co-occurrence of Bacteroides with lower expression of interleukin signaling pathways is supported by experimental work that found potential anti-inflammatory and protective roles for these bacteria in the context of intestinal inflammation [34,39,40]. Still, the relative contributions of each of these species, as well as their behavior in the context of intestinal inflammation, remains elusive, although our data might reflect an overrepresentation of anti-inflammatory members [34-39,43]. The positive associations between Bacteroides and expression of metal ion response genes and metallothioneins (MTs) are intriguing in the context of IBD because aberrant MT homeostasis and intracellular zinc metabolism have been implicated in disease pathophysiology [4448].…”
Section: Resultssupporting
confidence: 52%
“…That crypt-associated anomalies never reach the stadium of asymmetric branching as they are digested by mast cells and/or gut microbiome proteases 25 26…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, B. vulgatus has been shown to be protective against Escherichia coli induced colitis of interleukin-2-deficient gnotobiotic mice ( Waidmann et al, 2003 ). In contrast, several studies revealed that B. vulgatus is generally viewed as a pathobiont ( Ó Cuív et al, 2017 ), often associated with colitis in murine ( Bloom et al, 2011 ) model systems, as well as human ulcerative colitis ( Mills et al, 2022 ), irritable bowel disease ( Ryan et al, 2020 ), and celiac disease ( Schippa et al, 2010 ; Bloom et al, 2011 ; Wu et al, 2021 ). It has also been shown that B. vulgatus has an increased protease activity compared to other Bacteroides spp., and can cause barrier dysfunction ( Riepe et al, 1980 ; Mills et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%